WAVE HYDRODYNAMIC INTERACTION STUDY ON ARTIFICIAL REEF BREAKWATER - RAFLI, MUHAMMAD ASRAF (IRC, 2016)
Coastal areas have provided strategic and easy access from long distance and save time especially in onshore activities. Meanwhile, coastal areas continuously undergo dynamic processes with the contribution of two natural processes, which are erosion and accretion that shape the coastline. As long as no inteference from the man’s intervention, the coastline is actually stable. After many years, the rapid development and urban navigation at coastal area interfere both of process and led to erosion problem. The erosion problem can be controlled by implementing coastal structures. The construction of coastal structure may disturb the habitat of the aquatic life in the shallow area. In this project, the breakwaters were to be designed as the habitat for fish communities and combine with the concept of artificial reef that currently used in fish enhancement purpose.